Performance analysis of the working surface of the rails from test batches on the Test Loop of JSC “VNIIZhT” - M. Yu. Khvostik; I. V. Khromov; O. A. Bykova; G. A. Beresten’ (Вестник Научно-исследовательского института железнодорожного транспорта)
The monitoring of railway rails damage on the railway network of the JSC “Russian Railways” as well as operational and polygon tests are conducted with the purpose of assessing the impact of operating conditions on the intensity of rails damage, obtaining initial data for forecasting rails failures. The increased intensity of rails wear on sites with a complex plan and profile leads to the fact that with a continuous change from the track, rails which have an underutilized service life of more than 20 % are retrieved. Polygon tests on the Test Loop of the JSC “VNIIZhT” near the Scherbinka station can provide the repeatability and reliability of the results, comparative tests are carried out under identical conditions and their duration is several times less than when tested at experimental sites under operational conditions. The results of the polygon tests of new differentially heat-strengthened rails did not reveal any advantages in the wear resistance of special purposed rails (laid in the recommended radius of the curve for its application) when comparing the rails of domestic manufacturers. Metal shelling out on the rolling surface of rails is the main reason for the removal of rails from test batches. The origin and development of defects of this kind is due to both violations of the technology of manufacturing rails, and because of violations of the current maintenance of the track. The metal stock in the area of the rail head of R65 type due to the increase in its dimensions positively affects the extension of the lifetime of the rails, reducing the cost of the life cycle and the rail itself, and the design of the track as a whole. When carrying out a separate study in order to obtain results characterizing the stability of high-quality rails to contact fatigue damage, it is advisable to optimize the conditions of the polygon tests, bringing them closer to operational ones. When forming the test results, it is necessary to expand the list of criteria for assessing the wear resistance of rails, supplementing it with the size of the wear area at the time of a certain operating time of the tonnage, with the introduction of this criterion into the appropriate methods for the polygon (operational) tests.